O‘ZBEKISTONDA INFLYATSIYA MUAMMOSI VA UNI BARTARAF ETISH YO‘LLARI (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article analyzes the main causes of inflation in Uzbekistan, its impact on the economy and its problems. It also proposes effective measures to curb and stabilize inflation, solutions based on international experience and advanced methods. The article examines the theoretical foundations of inflation, its impact on economic processes, and the role of state policy.